Selective removal of hydroxyl groups from graphene oxide - Chua, Chun Kiang (2014)
Graphene has a wide range of potential applications, thus tremendous efforts have been put into ensuring that the most direct and effective methods for its large-scale production are developed. The formation of graphene materials from graphene oxide through a chemical reduction method is still one of the most preferred routes. Numerous methods starting from various reducing agents have been developed to obtain near-pristine graphene sheets. However, most of the reducing agents are not mechanistically supported by classical organic chemistry knowledge and of those that are supported, they are only theoretically capable of, at most, reducing oxygen-containing groups on graphene oxide to hydroxyl groups. Herein, we present a mechanistically proven method for the selective defunctionalisation of hydroxyl groups from graphene oxide that is based on ethanethiol–aluminium chloride complexes and provides a graphene material with improved properties. The structural, morphological and electrochemical properties of the graphene materials have been fully characterised based on high-resolution X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, scanning electron microscopy, electrochemical impedance spectroscopy and cyclic voltammetry techniques. Our analyses showed that the obtained graphene materials exhibited high heterogeneous electron-transfer rates, low charge-transfer resistance and high conductivity as compared to the parent graphene oxide. Moreover, the selective defunctionalisation of hydroxyl groups could potentially allow for the tailoring of graphene properties for various applications.